William Rice, A Digested Index of the Statute Law of South Carolina From the Earliest Period to the Year 1836, Inclusive 356 (Charleston 1838) - (:unkn) unknown (My University, 1835)
Prohibited any "free negro or other free person of color" from carry firearms without a ticket.
Keywords: ENSLAVED PERSONS & OTHER MINORITIES